Investigating palladium pincer complexes in catalytic asymmetric hydrophosphination and hydroarsination - Tay, Wee Shan (2021)
Given the periodic relationship of phosphines and arsines, is remodeling the catalytic asymmetric hydrophosphination reaction an efficient manner to develop the corresponding hydroarsination reaction? Herein, a chiral PCP-Pd(II) pincer complex adept at generating enantioenriched phosphines was examined in the asymmetric hydroarsination reaction. Under distinct conditions, tertiary phosphines and arsines were generated in excellent yields (P: 96%, As: 91%) and ees (P: 90%, As: 85%). While secondary arsine reagents were not direct substitutes for the analogous phosphines, important parameters were identified which increased yield and ee of the hydroarsination reaction. Unlike the PCP-PdOAc pincer complex commonly used for hydrophosphinations, hydroarsination reactions involved a PCP-PdCl catalyst with 10 equiv. of CsF for optimal performance. Notable differences between the two reactions and their workup procedures were highlighted to guide further developments in the field. Lastly, respective mechanisms were proposed and contrasted for the activation of HEPh₂ (E = P, As).